2019
DOI: 10.5624/isd.2019.49.1.53
|View full text |Cite
|
Sign up to set email alerts
|

Tc-99m hydroxymethylene diphosphonate scintigraphy, computed tomography, and magnetic resonance imaging of osteonecrosis in the mandible: Osteoradionecrosis versus medication-related osteonecrosis of the jaw

Abstract: Purpose To present characteristic findings of Tc-99m hydroxymethylene diphosphonate (HMDP) scintigraphy, computed tomography (CT), and magnetic resonance (MR) imaging for osteonecrosis in the mandible, especially osteoradionecrosis (ORN) and medication-related osteonecrosis of the jaw (MRONJ). Materials and Methods Thirteen patients with MRONJ and 7 patients with ORN in the mandible underwent Tc-99m HMDP scintigraphy, CT, and MR imaging (T1-weighted images [T1WI], T2-we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…16 Several previous studies have attempted to identify pathognomonic imaging features of MRONJ; however, most of those studies used 3-dimensional (3D) imaging modalities. 15,17,18 As panoramic radiography is typically used as part of the basic examination performed in dental clinics, we hypothesized that the early detection of signs of MRONJ using panoramic radiography, along with medication history, could be extremely helpful in diagnosing MRONJ. In the present study, sequestrum and extraction socket were observed significantly more frequently in the medication-related group.…”
Section: Resultsmentioning
confidence: 99%
“…16 Several previous studies have attempted to identify pathognomonic imaging features of MRONJ; however, most of those studies used 3-dimensional (3D) imaging modalities. 15,17,18 As panoramic radiography is typically used as part of the basic examination performed in dental clinics, we hypothesized that the early detection of signs of MRONJ using panoramic radiography, along with medication history, could be extremely helpful in diagnosing MRONJ. In the present study, sequestrum and extraction socket were observed significantly more frequently in the medication-related group.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were reported by Ogura et al, which could be distinguished from medication-related osteonecrosis of the jaw (MRONJ). MRONJ was often observed periosteum reaction and the periosteum condition of MRONJ is usually less damaged than that of ORN [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…One particular limitation of our study was the very high probability of BRONJ in patients we selected, so the specificities cited herein must be interpreted with some caution. Clearly, other disorders of mandible and maxilla, such as osteomyelitis [26], radionecrosis [27], and severe periodontitis [28], may similarly exact marked increases in polyphosphonate uptake, making it difficult to diagnose MRONJ on the basis of bone scan only. However, Ogura et al recently published two papers on use of quantitative SPECT/CT to discriminate MRONJ from other disorders of the jaw, primarily chronic osteomyelitis and osteoradionecrosis [27,29].…”
Section: Discussionmentioning
confidence: 99%